The Relationship between Learning Readiness and Learning Outcomes of Package C Students at PKBM Titian Amanah Kayu Tanam - Elvira Salman, Iza; Syur'aini, Syur'aini (Universitas Negeri Padang, 2024)
The purpose of study is to ascertain how adult student learning outcomes in Indonesian language classes at PKBM Titian Amanah relate to their readiness for learning. Attention, drive, and the growth of personal preparedness are all components of learning readiness. This study employed a correlational research design and a quantitative methodology. The questionnaire measures the level of learning readiness in terms of attention, motivation and development of individual readiness. Findings of this research indicate the learning readiness of adult students Package C program at PKBM Titian Amanah is in the low category, especially in terms of attention and motivation. This is evident from respondents' propensity to select